RANCANG BANGUN APLIKASI BELAJAR WEB HAKCING BERBASIS JEJARING SOSIAL (FACEBOOK) - Astamal, Rio; Sukmaaji, Anjik; Sutanto, Teguh (Jurnal JSIKA, 2013)
Knowledge of various web-based application security needed to build web applications that do not potentially have security flaws. To assist web developers in understanding various web vulnerabilities need to be provided special learning media. Simulation-based learning is used as learning strategy so the users can test applications directly; the goal is to make users know what kind of mistake that trigger the security flaw. Learning Web Hacking Application is web-based application that contains a series of questions about web technology and the vulnerabilities of web applications. Users can obtain the answer by hacking the web application that has been provided. The success of this process depends on how much the user´s understanding about the security of web application. Application also provides a feature called “Learning Center” which consist series of article to increase user knrowledge about web vulnerabilites and how to prevent it. Learning Web Hacking Application can be used to help the learning process on web application security and application can be integrated with Facebook and has social networking features so users or friends of the users in the circle of Facebook friends can be motivate to learn more about the security of web based applications.